Condições materiais no atendimento escolar à educação infantil no campo : região de Bragança Paulista/SP (2007 a 2015) - Preto, Mariany Cristina Fardin (Universidade Federal de São Carlos, 2017)
The purpose of this study is to describe the current conditions of the school support system that Brazilian Countryside Early Childhood Education students are provided with. This study was conducted at schools in the state of São Paulo, Brazil, in a period between 2007 and 2015. The study analyzed data samples of eight cities within the Regional Board of Education in the Bragança Paulista area. The data samples were collected in a micro-data database from Scholar Census. The eight cities within the Regional Board of Education in the Bragança Paulista area presented the highest school enrollment rates in the state of São Paulo. This study initially presents considerations about Brazilian Early Childhood Education and Countryside Education histories to contextualize the study and set the study’s goal. The study shifts focus to how Brazilian legislation assures the Countryside Early Childhood Education, verifies how the legislation prescribes the students’ rights and understands the influence of International Organizations in drawing up these documents. Lastly, the study analyzed the scholar micro-data in the proposed period, where it was assumed that there were improvements in the Early Childhood Education in the studied area. However many of the schools still lacked fundamental infrastructure conditions, physical resources and electronic devices. In conclusion, the study indicates the importance of educational policies that benefit countryside citizens and the Countryside Early Childhood Education as well as public educational funding to enable better quality regarding the Early Childhood Education.
Material conditions of the early childhood scholar attendance at the contrydise: Bragança Paulista Area / SP (2007 a 2015)
Keywords: Educação infantil; Educação do campo; Bragança Paulista (SP); Escola rural; Early childhood education; Countryside education; Countryside school; Rural schools; CIENCIAS HUMANAS::EDUCACAO